Diastereoselective Synthesis of Dispiropyrrolidinyloxindoles via DBU‐Promoted [3+2]‐Cycloaddition of Cyclic Pyridinium Ylides and α, β‐Unsaturated Ketones. Issue 1 (28th December 2022) - Liang, Xiayu; Wang, Bingren; Sun, Jiayang; Li, Yaqi; Zeng, Qingle
Abstract: A novel [3+2]‐cycloaddition reaction of cyclic pyridinium ylides and α, β‐unsaturated ketones derived from indanones for the synthesis of dispiropyrrolidinyloxindoles is described herein. Various types of dispiropyrrolidinyloxindoles can be conveniently accessed with moderate to good yields and up to >99 : 1 dr from easily available pyridinium salts which bear an electron‐withdrawing group on the pyridine ring under mild conditions for short reaction time. Abstract : The [3+2] annulation reaction between cyclic pyridinium ylide and unsaturated ketones has been developed, in which a series of novel dispiropyrrolidinyloxindoles with two meta‐quaternary carbon centers were obtained in moderate to good yields and up to >99 : 1 dr.